Social Cohesion and - Wanjogu, Joyce Karimi (My University, 2011)
Many models of development have been tried in Kenya and these include economic growth models, structural adjustment programmes, good governance and poverty reduction strategies. Largely, the results have not been as impressive as anticipated. Coupled with globalisation and rapid urbanisation and the adverse effects of these two on the society, there has emerged a pattern of social crisis manifested through rampant corruption, abuse, and waste. As a result, the promotion of social relations emerges as an alternative strategy to bring about development in Kenya in particular and the continent in general. The study seeks to understand how social cohesion and national identity shape and are shaped, through participation in sports. It also seeks to explore ways through which social cohesion can be enhanced through sport in Kenya. The study uses documentary review as the mode of research and data is gleaned from studies that have been undertaken in the country, the Kenyan Legislative framework as well as articles and reports in the mass media. The study found that, the country has not been successful in its efforts to address the cleavages that exist in the wider Kenyan society as a result of ethnicity, race, gender or economic differences. Moreover, sport is yet to be recognised as a viable vehicle which can drive the ideals of social cohesion to the people. Kenya’s draft sport’s policy does not deliberately articulate the role of sport in social cohesion and national identity and thus lacks a concrete way in which sport can be used effectively to promote these notions. The study recommends that there is urgent need to enact a sports policy that recognises the role of sport in enhancing social cohesion and that the development of sport in the country should be managed in such a way that the wider cleavages in the Kenyan society are not replicated.
MM - P&DM
Keywords: Social cohesion; Sport; Kenya